Efektivitas penggunaan media Screencast O-Matic pada mata kuliah kalkulus integral terhadap hasil belajar mahasiswa - Sinta Verawati Dewi (Program Studi Pendidikan Matematika, FKIP, Universitas Siliwangi, Tasikmalaya, 2016)
This research conducted to know the effectiveness of screencast-o-matic application against student learning outcomes. This research was quasi-experimental in Siliwangi University of Tasikmalaya. The data was analyzed by using SPSS 20.0 software. Based on Test Statistic table, the value of Exact sig. (1-tailed) 0,000 0,025, means Ho is rejected. This showed that the average of ranking of the experimental group significantly exceeded the average ranking of the control group. In other words, student learning outcomes which using Screencast-o-matic media was better than the student learning outcomes which using conventional learning. Results of this research were expected that the lecturer or teachers are able to apply Screencast-o-matic media in learning so that the lessons more effective.